Fejezetek a korai magyar privatizációk és államosítások történetéből, 17-18. század - Mihályi Péter (Hungarian Academy of Sciences, Institute of Economics, 2015)
– It was a great surprise to both the Hungarian and the international research community to see how determined and successful were the 2nd and the 3d Orbán-governments in rolling back the results of the post-communist privatizations. In my earlier papers - see Mihályi (2014, 2015a,b) - I showed that such renationalizations had occurred in other post-socialist countries as well, and discussed several, well-known property confiscation cases from the Hungarian history in the period 1848-1989. In the present paper, two events are recalled from earlier times - the 17th and 18th century, respectively. The first case study presents the largest-ever land privatization in Hungarian history, when the territories retaken by the Habsburgs from the Ottoman Empire were privatized (donated or sold) to the representatives of the loyal noble subjects of the Vienna court. The second case study reconstructs the details of large-scale nationalizations carried out by two Austro-Hungarian rulers - Maria Theresia and Joseph II - during the last three decades of the 18th century, when they abolished the majority of religious orders and confiscated all their assets. The punchline of the first case study is that we cannot understand the present renationalization wave in Hungary, if we do not take into account the poisonous historical legacy of the Hungarian feudalism. From the second case study we can learn that under certain conditions, the same objectives demand very similar means, even if the general historical conditions are entirely different; and the same notions - like privatization or nationalization - have entirely different meanings. As we show, the confiscation of the property of religious orders by Joseph II, enfolded in a strikingly similar way, as the communist nationalization of private companies in 1948.
Keywords: F52; N13; Q15; Z12; 330; Hungary; economic history; nationalization; privatization; land reform; Neoacquistica Commissio; abolition of religious orders